Stoichiometry modulated tunable optoelectronic properties of Nb-doped WS2 synthesized by chemical vapor deposition method - Caiyun Wang; Ziyue Liu; Gao Xiong (Scientific Reports, 2024)
Abstract Significant progress has been made in the field of two-dimensional WS2, yet the precise control of the doping process to achieve desired properties and the interpretation of complex physical phenomena in these novel materials necessitate thorough research. In this study, Nb-doped WS2 is synthesized using chemical vapor deposition technology, leading to triangular flakes with a side length of 12–20 μm. The X-ray photoelectron spectroscopy analysis indicates that the NbW substitution defect functions as an electron acceptor. The interlayer and transverse forces of the Nb-doped WS2 flake approach 1 nN and 150 pN, respectively. As the doping concentration increases, the valence band maximum energy of Nb-doped WS2 ranges from 4.06 eV to 4.3 eV. Furthermore, the performance of the photodetector is discussed.